Statistical optimization of cost-effective lignocellulosic medium for maximum xylanase activity by Massilia timonae B2YR - Thanekar, Rajani; Mali, Savita; Kamble, Prajakta; More, Vikramsinh; Sonawane, Kailas D.; Attar, Yasmin C. (Asia-Pacific Journal of Science and Technology, 2023)
Response surface methodology was used in the current study to optimise a lignocellulosic waste medium containing wheat bran (agro residue) and Pistia stratiotes (waterweed) for escalating xylanase activity using a bacterial isolate, Massilia timonae B2YR KY942185 screened from sawmill industry soil. After box behnken design (BBD) optimization, the medium composition was wheat bran 1.5 % w/v and Pistia 2 %w/v, demonstrating a 1.95-fold increase in xylanase activity. The xylanase enzyme was purified to 20.61-fold by Cellulose Diethylaminoethyl (DEAE) Chromatography with 32.60% recovery of enzyme activity. The molecular weight of xylanase was found to be 43 kiloDalton (kDa) by using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS PAGE). Mn, a metal ion, was found to increase xylanase activity (MnCl). Simultaneously, the enzyme demonstrated remarkable stability at acidic pH (4), with a retention of 75% in relative activity after 2 h of incubation in the corresponding pH buffer. Thus, the ideal conditions for maximum xylanase activity were 28± 2°C and pH 7. The kinetic experiments revealed a Michaelis menten constant for enzyme activity (Km)of 2.7 mg/mL and a maximum velocity of enzyme activity (Vmax) of 178.3 mol/min/mg. A crude xylanase fraction treatment on a Pistia and wheat bran mixture yielded 20.66mg of xylooligosaccharides after 18 h.